Method for preparing twin crystal enhanced coating through meniscus confinement electrodeposition and product thereof

Through the meniscus confined electrodeposition technology, the electrodeposition parameters are accurately controlled, and twin-reinforced coatings with excellent mechanical properties and conductivity are prepared, solving the problems of complex processes and difficult to optimize performance in the prior art.

CN119800465APending Publication Date: 2025-04-11ZHEJIANG UNIV OF TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510020163.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is complicated when preparing nanotwin structure plating layers, making it difficult to achieve precise control of twin grain size, and while improving mechanical strength, it is difficult to maintain substrate conductivity.

Method used

The meniscus limited-domain electrodeposition technology is used to accurately control electrodeposition parameters such as current, printing speed and ambient humidity, and the preparation of twin-enhanced plating is achieved, which simplifies the process flow and avoids the addition of additives.

Benefits of technology

Accurate control of twin grain sizes, optimize the mechanical properties and conductivity of the plating, improve the overall performance of the plating, and reduce production costs and operational complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800465A_ABST
    Figure CN119800465A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a twin crystal enhanced coating through meniscus confinement electrodeposition and a product thereof, and relates to the technical field of material science and electrochemistry, the method comprises the following steps: step 1, sequentially carrying out pretreatment and plasma treatment on a silicon wafer; 2, a mixed solution of metal salt and acid is prepared to serve as electrolyte, the electrolyte is transferred into a micro needle tube with a nozzle in a 3D direct-writing printing device, an anode is immersed into the electrolyte in the micro needle tube, the silicon wafer subjected to plasma treatment serves as a cathode, the anode and the cathode are connected with an external power source, direct current is applied to conduct 3D printing, and the 3D printing device is obtained. And the electrolyte forms a meniscus between the nozzle and the plasma-treated silicon wafer, and electro-deposition is carried out on the surface of the plasma-treated silicon wafer to form a twin crystal enhanced coating. The method disclosed by the invention is simple and convenient to operate, does not need to add auxiliaries, can realize accurate control of the size of the twin crystal grains, and improves the mechanical strength under the condition of not sacrificing the conductivity of the substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material science and electrochemical technology, and in particular to a method for preparing a twin-enhanced coating by confined electrodeposition of a curved liquid surface and a product thereof. Background Art

[0002] Nanotwin materials have a special microstructure and have received extensive attention from the materials science community due to their excellent mechanical properties and plasticity, outstanding thermal stability, high electrical conductivity, and work hardening effects. Twins refer to the mirror-symmetric orientation relationship between two crystals (or two parts of a crystal) along a common crystal plane. The formation of twins is closely related to stacking faults. Nanotwin materials can be prepared by a variety of methods, including magnetron sputtering physical deposition, electrodeposition, plastic deformation, and heat treatment. They have broad application prospects in the fields of aerospace, electronic devices, and biomedical materials.

[0003] Twins play a vital role in constructing microstructures with both excellent mechanical properties and outstanding conductive properties. The "electrochemical gradient" formed during dynamic electrodeposition can induce the formation of twins. For example, Chinese patent document No. CN112239874A discloses a pure nickel or nickel-based alloy coating with a nano-twin structure and an electrodeposition preparation method thereof. The plating solution used in the invention mainly includes a nickel source - nickel sulfate, an alloy source (sodium molybdate or cobalt sulfate or copper sulfate), a chelating agent - sodium citrate, and additives; the rest is water; the pure nickel and nickel alloy coatings prepared by direct current electrodeposition are composed of columnar grains, and the columnar grains contain high-density parallel-arranged twin lamellae, with an average twin lamella thickness ranging from 1.0nm to 100nm. The nano-twin nickel / nickel-based alloy coating has high hardness and high thermal stability. The Chinese patent document with publication number CN105803501A discloses a method for preparing a high-density twinned metal material, comprising the following steps: S1: select a metal sheet with good electrical conductivity, remove oil, rust and polish, and then use sandpaper to grind a number of parallel grooves on the surface of the metal sheet, with a flat convex strip between any two grooves, and the grooves and the convex strips are arranged at periodic intervals; S2: use a direct current electrodeposition method, select high-purity water or a metal salt solution as the electrolyte, and select the metal sheet polished in S1 for both the cathode and the anode for electrodeposition to obtain a high-density twinned metal material. The invention can obtain a high-density twinned metal material with a growth grain boundary spacing of 2-5nm and uniform distribution.

[0004] In the above electrochemical deposition process, additives need to be added to prepare a specific plating solution system or the surface resistance needs to be changed by fine-tuning the surface structure of the metal sheet to obtain a periodic current distribution, thereby obtaining a nano twin structure. The method or raw materials are relatively complex, and it is difficult to achieve precise control of the twin grain size. Summary of the invention

[0005] In order to address the deficiencies in the prior art, the present invention provides a method for preparing a twin-enhanced coating by curved liquid surface confined electrodeposition. The method is easy to operate, does not require the addition of additives, can achieve precise control of the twin grain size, and improves the mechanical strength without sacrificing the conductivity of the substrate.

[0006] The specific technical solutions adopted are as follows:

[0007] A method for preparing a twin-enhanced coating by confined electro-deposition of a meniscus, comprising the following steps:

[0008] Step 1, pre-treating and plasma treating the silicon wafer in sequence;

[0009] Step 2. Prepare a mixed solution of metal salt and acid as an electrolyte, transfer the electrolyte to the inside of a microneedle tube with a nozzle in a 3D direct writing printing device, immerse the anode in the electrolyte inside the microneedle tube, and use the plasma-treated silicon wafer as the cathode. The anode and the cathode are respectively connected to an external power supply, and direct current is applied while 3D printing is performed. The electrolyte forms a curved liquid surface between the nozzle and the plasma-treated silicon wafer, and a twin-enhanced coating is formed by electrodeposition on the surface of the plasma-treated silicon wafer.

[0010] The present invention is based on the curved liquid surface confined electrodeposition technology. By precisely controlling the electrodeposition parameters, the preparation of twin-enhanced coatings on the surface of silicon wafers is achieved. The core of this technology is to use the microenvironment formed by the curved liquid surface to limit the electrodeposition process, thereby forming a twin structure coating with excellent mechanical properties and electrical conductivity on the surface of the silicon wafer.

[0011] Preferably, the pretreatment method is ultrasonic cleaning to remove particles and macromolecular contaminants on the surface of the silicon wafer.

[0012] Preferably, the pretreated silicon wafer is placed in a plasma device, nitrogen is introduced, the gas flow rate is set to 40 sccm, and the plasma is bombarded for 90 to 150 seconds at a power of 200-500 W to perform plasma treatment on the pretreated silicon wafer.

[0013] Plasma treatment can roughen the surface of silicon wafers, remove surface oxides and improve the bonding strength between film and substrate.

[0014] The metal salt is selected from copper sulfate, cobalt sulfate or nickel sulfate, and the acid is selected from sulfuric acid, hydrochloric acid or nitric acid.

[0015] Preferably, in the electrolyte, the anion of the metal salt is the same as the acid ion.

[0016] Furthermore, in the electrolyte, the concentration of the metal salt is 0.05-0.5M, and the concentration of the acid is 0.01-0.1M. The concentration of the metal salt in the electrolyte directly affects the electrodeposition rate and the continuity of the coating. When the concentration is too high, the supply of metal ions is sufficient and the electrodeposition rate is fast, but it may cause the coating to be rough and form holes; when the concentration is too low, the electrodeposition rate is slow, affecting the production efficiency, and may cause the coating to be discontinuous; similarly, the concentration of the acid not only affects the efficiency of electrodeposition and the quality of the coating, but also affects the stability of the electrolyte and the safety of operation. High-concentration acid may aggravate the corrosion of the base material, increase the discharge of hydrogen ions, and cause the generated hydrogen bubbles to affect the density and adhesion of the coating; low-concentration acid may cause the conductivity of the electrolyte to decrease, affecting the electrodeposition rate and current efficiency, resulting in uneven coating, defects, and affecting the mechanical properties of the coating.

[0017] Optionally, the anode is a metal copper wire and the nozzle is a glass nozzle.

[0018] Preferably, the nozzle has a conical structure with a diameter of 2 to 10 μm, further 10 μm; the distance between the nozzle and the silicon wafer after plasma treatment is 3 to 5 mm, further 4 mm; direct current is applied to keep the current constant, the current is 5 to 50 nA, and the electrodeposition time is 200-1600 s.

[0019] Further preferably, the speed of 3D printing is 0.05-0.4 μm / s; during 3D printing, the ambient temperature is 24.5-25.5° C., and the ambient humidity is 50%-80%.

[0020] Specifically, the size of the twinned grains can be controlled by adjusting the electrodeposition parameters such as current, printing speed and ambient humidity, making it adjustable within the range of 5-150 nm.

[0021] Furthermore, after the electrodeposition process is completed, the surface is rinsed with deionized water to remove electrolyte residues.

[0022] The present invention also provides a twin-enhanced coating, which is prepared by the method for preparing the twin-enhanced coating by curved liquid surface confined electrodeposition; at the same time, the method can also be used in the fields of electronic devices, micro-electromechanical systems or structural reinforcement materials.

[0023] The twin-enhanced coating is composed of high-density twin lamellae, which are arranged in parallel along the (111) direction to form a microstructure with mirror symmetry. The size range of the twin grains is 5 to 150 nm. The thickness of the twin-enhanced coating is uniform and adjustable within the range of 0.4-1.2 μm. The coating surface is flat, the boundaries between the grains are clear, and there are no obvious holes and cracks, indicating that the electrodeposition process is well controlled.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The method of the present invention has advantages in terms of cost, ease of operation and deposition rate, and the plating solution (electrolyte) has a small amount of raw materials and does not require the addition of additives. The method has good applicability and is suitable for the preparation of various metal twin-enhanced coatings.

[0026] (2) The method of the present invention controls the size of the twin grains by adjusting the electrodeposition parameters, including current, printing speed and ambient humidity. The method of the present invention can achieve precise control of the twin grain size, thereby optimizing the performance of the metal twin-enhanced coating and improving the mechanical strength of the metal structure without reducing the conductivity (this performance is the difficulty in the preparation of existing coatings).

[0027] (3) The method of the present invention is of great significance for developing new potential applications in studying the basic principles and control strategies of DC electrodeposition of metal twin microstructures through curved liquid surface confined electrodeposition (MCED), and is expected to be applied to micro lithium-ion batteries and other aspects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the nozzle tip structure.

[0029] Figure 2 The figure is a schematic diagram of the circuit structure of the electrodeposition process of the method of the present invention.

[0030] Figure 3 This is a transmission electron microscope TEM image of the twin-enhanced coating prepared in Example 1.

[0031] Figure 4 This is a scanning electron microscope (SEM) image of the twin-enhanced coating prepared in Example 1.

[0032] Figure 5 This is a transmission electron microscope TEM image of the twin-enhanced coating prepared in Example 2.

[0033] Figure 6 This is a scanning electron microscope (SEM) image of the twin-enhanced coating prepared in Example 2.

[0034] Figure 7 This is a scanning electron microscope (SEM) image of the twin-enhanced coating prepared in Comparative Example 1. DETAILED DESCRIPTION

[0035] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description through specific embodiments. In the following description, many specific details are set forth in order to fully understand the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below. The technical features in each embodiment of the present invention can be combined accordingly without conflicting with each other.

[0036] The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer. The contents not described in detail in this specification belong to the prior art known to professionals in the field. The experimental materials used in the following examples, unless otherwise specified, can be purchased from conventional biochemical reagent companies.

[0037] The schematic diagram of the structure of the nozzle of the 3D direct writing printing device used in the present invention is as follows Figure 1 As shown, the circuit structure diagram of the electrodeposition process using a 3D direct writing printing device is as follows Figure 2 As shown, it can be obtained by simply modifying a conventional 3D direct writing printing device, and the nozzle is a glass nozzle.

[0038] Example 1 Preparation of twin-reinforced coating

[0039] The silicon wafer was cut into a square shape of 1 cm in length and 1 cm in width, and cleaned with an ultrasonic cleaner to remove surface particles and macromolecular pollutants. The cleaned silicon wafer was placed in a plasma device, nitrogen was introduced, and bombarded for 150 seconds at a power of 300 W. The cleaned silicon wafer was subjected to plasma treatment to roughen the surface of the silicon wafer, remove surface oxides, and improve the film-base bonding strength.

[0040] A mixed solution of 0.05M copper sulfate and 0.01M sulfuric acid was prepared as an electrolyte, and the electrolyte was transferred to the inside of a microneedle tube with a nozzle in a 3D direct writing printing device. The nozzle had a conical structure and a diameter of 10 μm. The nozzle was fixed above the plasma-treated silicon wafer, and the distance between the nozzle and the plasma-treated silicon wafer was 4 mm. The anode (the anode was a metal copper wire with a diameter of 0.25 mm) was immersed in the electrolyte inside the microneedle tube. The plasma-treated silicon wafer was used as the cathode. The anode and the cathode were respectively connected to an external power supply. Direct current was applied and 3D printing was performed simultaneously. The current was 30 nA, and the ambient temperature was maintained at 25°C. The ambient humidity was 65%, and the deposition printing speed was 0.2 μm / s. During the deposition process, the electrolyte formed a curved liquid surface between the nozzle and the plasma-treated silicon wafer, and a twin-enhanced coating was formed on the surface of the plasma-treated silicon wafer by electrodeposition. The deposition was completed after 400 s, and the product was taken out and rinsed with deionized water to remove the electrolyte residue on the surface.

[0041] like Figure 3 As shown in FIG, the cross-sectional morphology of the copper twin enhanced coating was observed using a transmission electron microscope (TEM), and it can be seen that the size of the twin grains is 5 nm. Figure 4 As shown, the morphology of the copper twin enhanced coating was observed using a scanning electron microscope (SEM). It can be seen that the roughness of the film surface is relatively high, the nucleation rate of the grains is slow, the nucleation sites are few and distributed relatively far apart, and the thickness of the copper twin enhanced coating is about 1.2 μm.

[0042] Example 2 Preparation of twin-enhanced coating

[0043] The silicon wafer was cut into a square shape of 1 cm in length and 1 cm in width, and cleaned with an ultrasonic cleaner to remove surface particles and macromolecular pollutants. The cleaned silicon wafer was placed in a plasma device, nitrogen was introduced, and bombarded at a power of 300 W for 150 s. The cleaned silicon wafer was subjected to plasma treatment to roughen the surface of the silicon wafer, remove surface oxides, and improve the film-base bonding strength.

[0044] A mixed solution of 0.05M copper sulfate and 0.01M sulfuric acid was prepared as an electrolyte, and the electrolyte was transferred to the inside of a microneedle tube with a nozzle in a 3D direct writing printing device. The nozzle had a conical structure and a diameter of 10 μm. The nozzle was fixed above the plasma-treated silicon wafer, and the distance between the nozzle and the plasma-treated silicon wafer was 4 mm. The anode (the anode was a metal copper wire with a diameter of 0.25 mm) was immersed in the electrolyte inside the microneedle tube. The plasma-treated silicon wafer was used as the cathode. The anode and the cathode were respectively connected to an external power supply. Direct current was applied and 3D printing was performed simultaneously. The current was 45 nA, and the ambient temperature was maintained at 25°C. The ambient humidity was 55%, and the deposition printing speed was 0.4 μm / s. During the deposition process, the electrolyte formed a curved liquid surface between the nozzle and the plasma-treated silicon wafer, and a twin-enhanced coating was formed by electro-deposition on the surface of the plasma-treated silicon wafer. The deposition was completed after 200 s, the product was taken out, and rinsed with deionized water to remove the electrolyte residue on the surface.

[0045] like Figure 5 As shown in the figure, the cross-sectional morphology of the copper twin-enhanced coating was observed using a transmission electron microscope (TEM), and an obvious flake twin structure was observed. The diffraction results of the corresponding area showed obvious double-point symmetrical diffraction spots, and the size of the twin grains was 150nm. Figure 6 As shown, the morphology of the copper twin enhanced coating was observed using a scanning electron microscope (SEM), which showed that the nucleation sites of the grains increased and the grains grew faster, making the deposited film more and more dense. The thickness of the copper twin enhanced coating was about 1 μm.

[0046] Example 3

[0047] The silicon wafer was cut into a square shape of 1 cm in length and 1 cm in width, and cleaned with an ultrasonic cleaner to remove surface particles and macromolecular pollutants. The cleaned silicon wafer was placed in a plasma device, nitrogen was introduced, and bombarded at a power of 300 W for 150 s. The cleaned silicon wafer was subjected to plasma treatment to roughen the surface of the silicon wafer, remove surface oxides, and improve the film-base bonding strength.

[0048] A mixed solution of 0.05M cobalt sulfate and 0.01M sulfuric acid was prepared as an electrolyte, and the electrolyte was transferred to the inside of a microneedle tube with a nozzle in a 3D direct writing printing device. The nozzle had a conical structure and a diameter of 4μm. The nozzle was fixed above the plasma-treated silicon wafer, and the distance between the nozzle and the plasma-treated silicon wafer was 4mm. The anode (the anode was a metal copper wire with a diameter of 0.25mm) was immersed in the electrolyte inside the microneedle tube. The plasma-treated silicon wafer was used as the cathode. The anode and the cathode were respectively connected to an external power supply. Direct current was applied and 3D printing was performed simultaneously. The current was 15nA, and the ambient temperature was maintained at 25°C. The ambient humidity was 70%, and the deposition printing speed was 0.2μm / s. During the deposition process, the electrolyte formed a curved liquid surface between the nozzle and the plasma-treated silicon wafer, and a twin-enhanced coating was formed on the surface of the plasma-treated silicon wafer by electrodeposition. The deposition was completed after 400s, the product was taken out, and rinsed with deionized water to remove the electrolyte residue on the surface.

[0049] The surface roughness of the cobalt twin-reinforced coating prepared in this embodiment is 10.1 nm, and the twin grain size is 30-50 nm.

[0050] Comparative Example 1

[0051] The silicon wafer was cut into a square shape of 1 cm in length and 1 cm in width, and cleaned with an ultrasonic cleaner to remove surface particles and macromolecular pollutants. The cleaned silicon wafer was placed in a plasma device, nitrogen was introduced, and bombarded at a power of 300 W for 90 seconds. The cleaned silicon wafer was subjected to plasma treatment to roughen the surface of the silicon wafer, remove surface oxides, and improve the film-base bonding strength.

[0052] A mixed solution of 0.1M copper sulfate and 0.05M sulfuric acid was prepared as an electrolyte, and the electrolyte was transferred to the inside of a microneedle tube with a nozzle in a 3D direct writing printing device. The nozzle had a conical structure and a diameter of 10 μm. The nozzle was fixed above the plasma-treated silicon wafer, and the distance between the nozzle and the plasma-treated silicon wafer was 4 mm. The anode (the anode was a metal copper wire with a diameter of 0.25 mm) was immersed in the electrolyte inside the microneedle tube. The plasma-treated silicon wafer was used as the cathode. The anode and the cathode were respectively connected to an external power supply. Direct current was applied and 3D printing was performed simultaneously. The current was 60 nA, and the ambient temperature was maintained at 25°C, the ambient humidity was 55%, and the deposition printing speed was 0.4 μm / s. During the deposition process, the electrolyte formed a curved liquid surface between the nozzle and the plasma-treated silicon wafer, and a twin-enhanced coating was formed on the surface of the plasma-treated silicon wafer by electrodeposition. The deposition was completed after 200 s, the product was taken out, and rinsed with deionized water to remove the electrolyte residue on the surface.

[0053] like Figure 7 As shown, the morphology of the copper twin-enhanced coating was observed using a scanning electron microscope (SEM). Due to the excessive current, the newly deposited metal accumulated in the printing area, resulting in the unevenness of the printed structure and the generation of surface defects.

[0054] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a twin-enhanced coating by confined electroplating of a meniscus, characterized in that: The following steps are involved: Step 1, pre-treating and plasma treating the silicon wafer in sequence; Step 2. Prepare a mixed solution of metal salt and acid as an electrolyte, transfer the electrolyte to the inside of a microneedle tube with a nozzle in a 3D direct writing printing device, immerse the anode in the electrolyte inside the microneedle tube, and use the plasma-treated silicon wafer as the cathode. The anode and the cathode are respectively connected to an external power supply, and direct current is applied while 3D printing is performed. The electrolyte forms a curved liquid surface between the nozzle and the plasma-treated silicon wafer, and a twin-enhanced coating is formed by electrodeposition on the surface of the plasma-treated silicon wafer.

2. The method for preparing twin-enhanced coating by meniscus confined electrodeposition according to claim 1, characterized in that: The pretreatment method is ultrasonic cleaning.

3. The method for preparing twin-enhanced coating by meniscus confined electrodeposition according to claim 1, characterized in that: The pretreated silicon wafer is placed in a plasma device, nitrogen is introduced, and the plasma is bombarded for 90 to 150 seconds at a power of 200 to 500 W to perform plasma treatment on the pretreated silicon wafer.

4. The method for preparing twin-enhanced coating by meniscus confined electrodeposition according to claim 1, characterized in that: The metal salt is selected from copper sulfate, cobalt sulfate or nickel sulfate, and the acid is selected from sulfuric acid, hydrochloric acid or nitric acid.

5. The method for preparing twin-enhanced coating by meniscus confined electrodeposition according to claim 1, characterized in that: In the electrolyte, the anion of the metal salt is the same as the acid radical ion.

6. The method for preparing twin-enhanced coating by meniscus confined electrodeposition according to claim 1, characterized in that: In the electrolyte, the concentration of the metal salt is 0.05-0.5M, and the concentration of the acid is 0.01-0.1M.

7. The method for preparing twin-enhanced coating by meniscus confined electrodeposition according to claim 1, characterized in that: The nozzle aperture is 2-10 μm; the distance between the nozzle and the silicon wafer after plasma treatment is 3-5 mm; direct current is applied to keep the current constant, the current is 5-50 nA, and the electrodeposition time is 200-1600 s.

8. The method for preparing twin-enhanced coating by meniscus confined electrodeposition according to claim 1, characterized in that: The speed of 3D printing is 0.05-0.4 μm / s; during 3D printing, the ambient temperature is 24.5-25.5°C, and the ambient humidity is 50%-80%.

9. A twinning enhanced coating, characterized in that: The coating is prepared by the method for preparing a twin-enhanced coating by curved liquid surface confined electrodeposition as described in any one of claims 1 to 8.

10. The twinning enhanced coating according to claim 9, characterized in that: The thickness of the twin crystal reinforcement coating is 0.4-1.2 μm; the size of the twin crystal grains is 5-150 nm.

Citation Information

Patent Citations

  • Preparation method for high-density twin crystal metal material

    CN105803501A

  • Pure nickel or nickel-based alloy plating layer with nano twin crystal structure and electro-deposition preparation method of pure nickel or nickel-based alloy plating layer

    CN112239874A

  • Single inhibitor for high aspect ratio TSV copper plating and electroplating process

    CN119101963A